Primary school headteacher recruitment and selection in England: the processes and the problematic aspects. (20th October 2019) - James, Chris; Fitzgerald, Sarah; Fellows, Tom; Goodall, Janet; Batlle, Ioannis Costas; Jones, Jeff
ABSTRACT: Appointing a headteacher in England is important but under-researched, hence the study reported here. We interviewed and surveyed chairs of governing boards that had recently undertaken the appointment process. Governing bodies follow broadly similar recruitment and selection processes, which have a number of problematic aspects: the unique nature of the context; the complexity of the processes; ensuring adequate recruitment; the processes are demanding, resource intensive, a considerable responsibility and difficult to organise especially when there are internal candidates; the skills required are specialised; engaging external expertise can be beneficial, but not without challenges; and the chair's involvement is typically substantial.